Cybersecurity in Smart Cities: Challenges and Solutions - Mazumder, Anindya (My University, 2020)
Smart cities are the cities of the future. Smart cities encourage the use of technology, information, and data to boost and upgrade their infrastructure and services. The main goal of a smart city is the well-being of the citizens. To achieve that, a smart city uses Smart features and applications to smarten its services. While this is immensely effective in making citizens' lives better, it poses a challenge to cybersecurity and data privacy. This thesis explores the cybersecurity challenges in smart cities, states their impact, and proposes probable solutions to solve the challenges and a guideline for further improvement in the security arena. Moreover, this thesis discusses the possible cyber-attacks and threats and common cybersecurity problems in a Smart City. Furthermore, it describes how standard development processes, proper technology selection, and cybersecurity culture help secure smart cities.
Keywords: Smart City, Smart Applications, Cybersecurity, Cybersecurity Challenges, Cyber attacks, IoT, Data Security, Smart People, Secure Development Lifecycle, DevSecOps, Cybersecurity Culture, Zero Trust Architecture